Spatial Distribution and Landscape Characteristics of Flores Hawk-Eagle (Nisaetus Floris) Habitat in Flores Island : Distribusi Spasial dan Karakteristik Lanskap Habitat Elang Flores (Nisaetus Floris) di Pulau Flores - Raja Mohd Kris Setiawan; Syartinilia - (Graduate School Bogor Agricultural University (SPs IPB), 2021)
Flores Hawk-Eagle (FHE, Nisaetus floris) is one of the endemic and keystone species that was rarely studied among other eagles. The study on the FHE is currently experiencing limited information for estimating their distribution area. Therefore, the FHE habitat distribution is required as the essential information for developing the strategies and conservation action. The objectives of this study were to identify the spatial habitat distribution and analyze the characteristics of the habitat. Minimum convex polygon (MCP) and kernel-density estimation (KDE) 95% was combined with the land cover map for delineating the patch habitat of FHE. Slope, elevation, and land cover were used as environmental variables. Principal Component Analysis (PCA) combine with GIS were used for characterizing the landscape habitat. The results showed that there were eight habitat patches with a total area of 1.132 km2. Six principal components were retained from PCA analysis which explained 71.96% of data variance. Habitat characteristics of FHE describe its requirement for nesting and hunting activities for principal components 1 to 4, while for flight activity related to principal components 5 and 6. Forests and savannahs become the main habitat preference for both nesting and hunting activities. Results of this study will be supported as baseline information for developing conservation strategies and action for FHE.